Description of the Knowledge Level on Seborrheic Dermatitis Among Medical Students at Universitas Sumatera Utara, Class of 2021 - 2023 - Lubis, Nova Zairina; Qoni'ah, Hanan (Talenta Publisher, 2025)
Background: Seborrheic Dermatitis (SD) is a chronic and recurrent inflammatory skin disease that commonly affects adolescents and adults, with a relatively high prevalence, particularly among immunocompromised individuals. SD has a multifactorial pathophysiology, involving Malassezia spp., skin surface lipids, and immunological dysregulation. This condition can significantly impact patients'quality of life due to frequent relapses, causing symptoms such as itching and redness. Therefore, prompt treatment with various available topical therapies is crucial. Objectives: This study aims to assess the level of knowledge about SD among medical students at the Faculty of Medicine, Universitas Sumatera Utara, from the class of 2021 – 2023. Methods: This is a descriptive study using a cross-sectional design, employing a questionnaire distributed via Google Forms and QR codes to students from the specified batches. The sampling technique used was simple random sampling. Results: The results showed that most students had a moderate level of knowledge about SD (50%). A total of 150 respondents (57.7%) had a sufficient understanding of SD treatment options. The majority of respondents were female students, with 176 responses. The age group of 17 to 20 years dominated the sample, accounting for approximately 46.2%. The highest number of respondents came from the 2021 cohort (67.3%). Conclusion: This study concludes that medical students at Universitas Sumatera Utara have a moderate level of knowledge regarding SD and its treatment options. These findings highlight the importance of further education and awareness to enhance students' understanding of the condition. Keyword: level of knowledge, seborrheic dermatitis, treatment selection Latar Belakang: Dermatitis seboroik (DS) adalah penyakit inflamasi kulit kronis dan rekuren yang sering terjadi pada remaja dan dewasa, dengan prevalensi yang cukup tinggi, terutama pada individu dengan kondisi imunokompromais. DS memiliki patofisiologi multifaktorial, yang meliputi Malassezia spp., lipid permukaan kulit, dan disregulasi imunologis. Penyakit ini dapat memengaruhi kualitas hidup penderitanya karena gejala yang sering kambuh, seperti gatal dan kemerahan. Oleh karena itu, pengobatan segera dengan berbagai pilihan terapi topikal yang tersedia sangat penting. Tujuan: Studi ini bertujuan untuk mengetahui gambaran tingkat pengetahuan tentang DS pada mahasiswa Fakultas Kedokteran Universitas Sumatera Utara angkatan 2021-2023. Metode: Penelitian ini bersifat deskriptif dengan desain potong lintang (cross-sectional), menggunakan kuesioner yang disebarkan melalui Google Form dan QR Code kepada mahasiswa/i Fakultas Kedokteran Universitas Sumatera Utara angkatan 2021-2023. Teknik pengambilan sampel menggunakan metode simple random sampling. Hasil: Hasil menunjukkan bahwa sebagian besar mahasiswa memiliki tingkat pengetahuan yang cukup mengenai DS (50%). Sebanyak 150 responden (57,7%) memiliki tingkat pengetahuan yang cukup terkait pemilihan pengobatan DS. Mayoritas responden adalah mahasiswi perempuan, dengan 176 respons. Kelompok usia 17 hingga 20 tahun mendominasi dengan persentase sekitar 46,2%. Responden terbanyak berasal dari angkatan 2021 (67,3%). Kesimpulan: Studi ini menyimpulkan bahwa mahasiswa Fakultas Kedokteran Universitas Sumatera Utara memiliki tingkat pengetahuan yang cukup mengenai DS dan pilihan pengobatannya. Temuan ini menekankan pentingnya peningkatan edukasi dan kesadaran untuk memperdalam pemahaman mahasiswa tentang kondisi ini. Keyword: dermatitis seboroik, pemilihan pengobatan, tingkat pengetahuan